Phospholipid-bound Tissue Factor Modulates both Thrombin Generation and APC-mediated Factor Va Inactivation - Váradi, Katalin; Siekmann, Jürgen; Turecek, Peter L.; Schwarz, H. Peter; Marder, Victor J. (Thrombosis and Haemostasis, 1999)
Hemostasis is initiated by tissue factor (TF) exposed on cellular phospholipid (PL) membranes, leading to thrombin generation. The binding of thrombin to thrombomodulin (TM), activates the protein C pathway, resulting in the inactivation of factors Va and VIIIa by activated protein C (APC) and a negative feedback effect on thrombin generation. A new assay system was developed for simultaneous measurement of thrombin and APC generation in defibrinated plasma induced by large unilamellar PL vesicles complexed with full-length recombinant TF (TF:PL). TF:PL preparations with a low TF concentration induced an initial rate of thrombin generation below 100 nM/min, and resulted in less thrombin formation in the presence of TM than in its absence. In contrast, TF:PL preparations with a high concentration of TF induced a higher rate of thrombin generation, and APC-mediated feedback inhibition did not occur, despite maximal APC generation. We used the same TF:PL surfaces to study factor Va inactivation by APC in a non-plasma reaction system, and found an inverse correlation between TF surface density and the rate of factor Va inactivation. This observation suggests a previously unrecognized hemostatic effect of TF, namely a non-enzymatic surface density-based inhibition of the anticoagulant effect of APC. In this model, high concentrations and surface density of TF exert complementary effects by promoting the regular procoagulant cascade and by inhibiting the protein C pathway, thereby maximizing hemostasis after vascular injury.
Keywords: Tissue factor; thrombin generation; factor Va; activated protein C